1977
DOI: 10.1073/pnas.74.8.3471
|View full text |Cite
|
Sign up to set email alerts
|

Biological properties of poliovirus encapsulated in lipid vesicles: antibody resistance and infectivity in virus-resistant cells.

Abstract: We present evidence that poliovirus can be encapsulated in synthetic large phospholipid vesicles. The virus associated with the vesicles is found to be (i) resistant to antiserum against poliovirus and (ii) infectious for cells that are normally resistant to virus infection because of a membrane restriction. Our interpretation of these results is that the virus is entrapped in the interior aqueous space of the vesicles and that this vesicle-associated virus is introduced directly into the cytoplasm of the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

1980
1980
1996
1996

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…In the course of studies dealing with synthetic lipid vesicles as vehicles for introduction of foreign materials into eukaryotic cells, poliovirus particles were experimentally encapsulated within synthetic large phospholipid vesicles. Such encapsulated particles are resistant to type-specific antiserum and are infectious for cells that normally resist infection because of a membrane restriction (107). The occurrence of such encapsulation during viral replication in nature may be the underlying mechanism causing virus aggregation and the phenomenon of a non-neutralizable fraction of picornaviruses.…”
Section: Properties Of the Enterovirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the course of studies dealing with synthetic lipid vesicles as vehicles for introduction of foreign materials into eukaryotic cells, poliovirus particles were experimentally encapsulated within synthetic large phospholipid vesicles. Such encapsulated particles are resistant to type-specific antiserum and are infectious for cells that normally resist infection because of a membrane restriction (107). The occurrence of such encapsulation during viral replication in nature may be the underlying mechanism causing virus aggregation and the phenomenon of a non-neutralizable fraction of picornaviruses.…”
Section: Properties Of the Enterovirusesmentioning
confidence: 99%
“…The buffalo green monkey (BGM) line of African green monkey kidney cells has been reported (17,107) as being more sensitive than primary rhesus or green monkey kidney cells for titration of certain enterovirus types and also for recovery of plaque-forming enteric viruses from sewage and water. However, comparative tests with clinical specimens indicated that the line may have limitations in sensitivity for routine isolation of a variety of echovirus types, as compared to primary rhesus monkey kidney and human fetal diploid kidney cells (96).…”
Section: Properties Of the Enterovirusesmentioning
confidence: 99%
“…These concerns have prompted the search for nonviral DNA transfection conditions for many cell types. Although nonviral techniques have overcome some of the problems of the viral systems, there remains a need for improved transfection efficiency in these newer nonviral systems (7, 13), although improved efficiency can be variably attained by the promoter enhancer elements utilized in the plasmid DNA constructs (19).As a nonviral system, liposomes have been used to encapsulate and deliver to cells a variety of materials, including nucleic acids (3-5) and viral particles (6,7,18,29). Recently, positively charged liposomes containing the membrane fusion- Of the viral vector systems, the recombinant adeno-associated virus (AAV) transduction system has proven to be one of the most efficient vector systems to stably carry the genes with high efficiency into a variety of mammalian cell types (17).…”
mentioning
confidence: 99%
“…As a nonviral system, liposomes have been used to encapsulate and deliver to cells a variety of materials, including nucleic acids (3-5) and viral particles (6,7,18,29). Recently, positively charged liposomes containing the membrane fusion- Of the viral vector systems, the recombinant adeno-associated virus (AAV) transduction system has proven to be one of the most efficient vector systems to stably carry the genes with high efficiency into a variety of mammalian cell types (17).…”
mentioning
confidence: 99%
“…To make these results more valid, it is necessary to solve two problems: effective passage of the labeled antibodies through the membrane, and sufficient fixation of the antigen. The replication of poliovirus which was introduced into virus-resistant cells by a fusion technique has been reported (3,13). Although the present study does not provide an optimistic finding concerning the liposomal infusion into the cytoplasm, this technique for binding HBsAg to cultured cells may be applicable to certain experimental systems, for it can cause the majority of cells to have HBsAg on their surface.…”
Section: Quantitative Assessment Of the Adherent Hbsag On Hela Cellsmentioning
confidence: 78%